Safe spaces for youth mental health: A scoping review - Salima Meherali; Saba Nisa; Yared Asmare Aynalem; Adeyinka G. Ishola; Zohra Lassi (PLoS ONE, 2025)
Introduction Mental illness is a significant challenge during adolescence and youth period, posing a threat to individuals’ mental health, well-being, and productivity. Despite the global burden, comprehensive evidence on the use of youth-safe spaces to improve their mental health has been limited. Therefore, this review aims to explore the existing literature on the role of safe spaces in shaping the mental health outcomes of youth. Methods We followed the Joanna Briggs Institute (JBI) scoping review guidelines. This review focused on individuals aged 10 to 25. It explores safe spaces for youth, including community centers, schools, clubs, and online forums, and their role in promoting youth mental health. We conducted a comprehensive search using PubMed/MEDLINE, PsycINFO, Web of Science, Scopus, Google Scholar, and grey literature sources. Study selection and screening were done using Covidence software, with two independent reviewers applying predefined criteria. We used the standardized table for data extraction; findings were presented using graphical and tabular formats alongside narrative synthesis. Reporting followed the PRISMA extension for scoping reviews (PRISMA-ScR) framework. Results The review included 23 studies from various regions, notably North America (USA) and Europe. These studies found that safe spaces, primarily within schools, offered youth mental health support, resources, and guidance. Additionally, community organizations, outreach programs, and primary care clinics were identified as safe spaces to enhance the mental well-being of young adults. The interventions used in these safe spaces included cognitive-behavioral therapy, mindfulness programs, and multi-component approaches. Positive outcomes included reduced posttraumatic stress disorders, anxiety, and substance use, along with improved mental well-being and interpersonal relationships. However, there needs to be more focus on methodological diversity and research in other regions. Geographic imbalances exist, and evidence beyond schools and communities as safe spaces is limited. Intersectional factors are often overlooked. Conclusion This review emphasizes the significant impact of safe spaces on youth mental health. It suggests that fostering supportive environments within schools, recreational clubs, and communities can significantly benefit youth mental well-being. The findings highlight the need to expand safe space initiatives to address young people’s challenges during their developmental stage.